2011
DOI: 10.1021/nl202721q
|View full text |Cite
|
Sign up to set email alerts
|

Compact Zwitterion-Coated Iron Oxide Nanoparticles for Biological Applications

Abstract: The potential of superparamagnetic iron oxide nanoparticles (SPIONs) in various biomedical applications, including magnetic resonance imaging (MRI), sensing, and drug delivery, requires that their surface be derivatized to be hydrophilic and biocompatible. We report here the design and synthesis of a compact and water-soluble zwitterionic dopamine sulfonate (ZDS) ligand with strong binding affinity to SPIONs. After ligand exchange, the ZDS coated SPIONs exhibit small hydrodynamic diameters (HD), and stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
213
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(217 citation statements)
references
References 28 publications
2
213
2
Order By: Relevance
“…This has been exploited to develop 10 nm-sized zwitterionic SPIONPs sing a compact DOPA sulfonate ligand (structure 3, Figure 2) [28][29][30].…”
Section: Sulfobetaine Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been exploited to develop 10 nm-sized zwitterionic SPIONPs sing a compact DOPA sulfonate ligand (structure 3, Figure 2) [28][29][30].…”
Section: Sulfobetaine Derivativesmentioning
confidence: 99%
“…Zwitterionization of SPIONPs has arisen as a powerful tool to improve their potential in nanomedicine. Among zwitterionic ligands, SB derivatives have been widely exploited to enhance the stability of SPIONPs [28][29][30]75]. Thus, Stephan et al…”
Section: Superparamagnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…After synthesizing the above inorganic core SPIONs, the native hydrophobic oleic acid coating was exchanged with a zwitterionic dopamine sulfonate (ZDS) that we have previously developed and described (35,37). Our prior studies have demonstrated that ZDScoated SPIONs show small HDs, low nonspecific interactions in vitro with cells and in vivo in mice, offering the opportunity for specific labeling, and stability with respect to time, pH, and salinity.…”
mentioning
confidence: 99%
“…Similarly, nanoparticles grafted with dendritic or hyperbranched PEG provide higher colloidal stability despite a smaller hydrodynamic radius as compared to linear PEG of similar MW [88]. The terminal end of PEG can be further functionalized with various bioligands to further decorate the surface of the PEG-coated nanoparticles for specific cell targeting, therapeutic treatment, and controlled drug delivery [83,89,90]. …”
Section: Grafting Catechol-polymer Conjugatementioning
confidence: 99%